Team handball : steps to success - Clanton, Reita E., 1952-; Dwight, Mary Phyl, 1951- (Champaign, IL : Human Kinetics, 1997)
Ilustrations, diagrams, and text combine to provide instruction in the game of team handball, covering passing and catching, piston movement and side stepping, dribbling, shooting, goalkeeping, defense, and other aspects of the sport.
Includes bibliographical references (p. 157).
Adult
Keywords: Team handball; Team handball